Near and similar restaurants: competitors or allies? - Pérez-Campdesuñer,Reyner (2020)
The proximity of businesses targeting the same market segment, meeting the same needs and operating in a similar way is generally believed to indicate more competition. However, this situation can be beneficial for the companies involved, and it may not necessarily generate an adverse environment. This study sought to analyse a group of restaurants that operate under similar conditions and that are located within the same area in order to identify the potential benefits and drawbacks of choosing this strategy to deal with market pressures. The research was based on a sample of 1,358 customers from 52 small restaurants. Diverse information-gathering techniques were combined such as observations, interviews and surveys. The data gathered was used to characterise different groups of variables behaviour based on descriptive statistics. In addition, bivariate statistics were utilised to test the hypotheses, while multivariate statistics were used to conduct correspondence analysis. The results reveal that, in the cases analysed, the parties involved benefit from the existing condition when a process of distribution of demand is present and advertising expenses are minimised.